STUDY IN THE POTENTIAL OF CHEMICAL COMPOUNDS OF ROSELLA FLOWER (HIBISCUS SABDARIFFA LINN) EXTRACT AS A PREVENTION OF RELAPSE AFTER ORTHODONTIC TREATMENT - Kusparmanto, Farhany Sefina; Pakpahan, Evie Lamtiur; Yuditha, Solva; Kusparmanto, Lukas (Universitas prof. Dr. Moestopo (Beragama), 2024)
In dentistry, we can correct malocclusion and malposition by moving the teeth with orthodontic treatment. After the orthodontic treatment is done there’ll still be a possibility of relapse. Relapse is when the teeth return to their original position before the orthodontic treatment was done. The prevalence of relapse after orthodontic treatment is still quite high. Relapse prevention can be achieved through the use of mechanical devices but, they have some limitations. Natural materials can be used as an alternative as the prevention method that can prevent the relapse from happening. Roselle extract contains chemical compounds that have the potential to prevent relapse after the orthodontic treatment is done. To observe the potential of chemical compounds in roselle flower extract as a relapse prevention method after orthodontic treatment. This research was a laboratory experiment. The research phase began with the extraction of rosella flowers (Hibiscus sabdariffa Linn), then continued with the second stage, namely the phytochemical screening of rosella flowers (Hibiscus sabdariffa Linn) using the color reaction method. The phytochemical tests showed that the roselle flower extract contains chemical compounds such as flavonoids, tannins, and saponins. Conclusion: The roselle flower extract contains chemical compounds such as flavonoids, tannins, and saponins, which have anti-inflammatory and antioxidant properties, making it potentially effective in preventing relapse after orthodontic treatment.